State Plan Proposals 1971-72 Government of West Bengal - Planning Commission (Planning Commission, 1971)
Among the States of India, West Bengal is thus the hardest hit by population explosion. the composition of the population has added to its difficulties. of the 349 lakhs of population in 1961, 22.39 lakhs (6.4%) were immigrants from other States, while only 6.06 (1.7%) lakhs had emigrated out. In addition to these another 38.25 lakhs of displaced persons from East Pakistan are estimated to have migrated to West Bengal by August, 1967 - their percentage being about 9.6 on the projected population of 1966.
Government of West Bengal, Development and Planning Department